1971
DOI: 10.1021/ja00738a031
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry and oxidation-reduction reactions of tin porphyrins

Abstract: An investigation of the chemistry and interconversion of tin(II) and tin(IV) porphyrins is reported. Tin(IV) porphyrins photoredu'ce with SnCl2• 2H20 in pyridine to yield first the tin(IV) chlorin and subsequently the corresponding r/c-tetrahydroporphyrin or bacteriochlorin. The mechanism of the photoreduction evidently involves electron transfer from SnCl2 to the porphyrin excited triplet and subsequent protonation of the resulting tin(IV) porphyrin dianion. Preparation of heretofore unknown tin(II) porphyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 2 publications
(2 reference statements)
0
25
0
Order By: Relevance
“…In the SnTPPS/wool fiber system, the color changed from purple to green after finishing the first hydrogen evolution reaction. Whitten et al reported that the tin (IV) porphyrin complexes are purple, while tin (II) complexes are green [18]. Tin (II) porphyrin was instable and had a low reduction property compared with the tin (IV) porphyrin [19].…”
Section: Photoinduced Hydrogen Evolution System Using Sntpp and Sntppmentioning
confidence: 99%
“…In the SnTPPS/wool fiber system, the color changed from purple to green after finishing the first hydrogen evolution reaction. Whitten et al reported that the tin (IV) porphyrin complexes are purple, while tin (II) complexes are green [18]. Tin (II) porphyrin was instable and had a low reduction property compared with the tin (IV) porphyrin [19].…”
Section: Photoinduced Hydrogen Evolution System Using Sntpp and Sntppmentioning
confidence: 99%
“…The proton source in the SnC12.2H20/pyridine reactions is the water of hydration; deuterium incorporation, predominantly into the bridge positions, results when SnCI2.2D20 is used. 55 The reaction proceeds with very low quantum efficiency when the octaalkylporphyrin complexes are used. ss When MS-tctraphenylporphyrin tin (IV) is the substrate the quantum yield is approximately I00 times greater, s8 Although tetraphenylporphyrin complexes are generally easier to reduce than the corresponding octaalkylporphyrins, g8 the greater case of reduction does not appear itself to simply account for the greater efficiency since under the reaction conditions used even the octaethylporphyrin tin (IV) triplet is more than 903 quenched by SnCl2.…”
Section: Photoreduction and Oxidation Of The Porphyrin Ringmentioning
confidence: 99%
“…The chemical shift values for both the methine and methylene protons fall in the ranges characteristic for di-and tetrapyrrolic compounds in which an aromatic macrocycle is lacking. The chemical shift value of 7.42 ppm assigned to the a-methine proton corresponds satisfactorily to the methine resonances in zinc porphodimethenes obtained by reductive methylation of zinc porphyrins [7.05 for a,,ydimethyl-a,'y-dihydro-octaethyl-porphyrin-zinc in C62H6 (10), (10) and photochemical (11)(12)(13) reduction of metalloporphyrins and phlorins (14). Reductive methylation of various octaethylporphyrin metal complexes yields a,'y-dihydro-a,'y-dimethyl porphyrins (10).…”
Section: Experimental Methodsmentioning
confidence: 53%
“…Recently, one of the isomers obtained by Krasnovskii reduction of zinc-a,'y-dimethyloctamethylporphyrin was isolated and characterized by 1HMR as the a,'y-dihydroproduct (11). Reduction at opposite sites is also probable for the photoreduction of zinc pheoporphyrins with ascorbic acid (12), and there is spectroscopic evidence that similar products are formed during the reaction of tin(IV) octaethylporphyrin with tin-(II) (13). Opposite methine positions, therefore, appear to be principal points of attack in metalloporphyrins, although other reduction pathways are known (15)(16)(17) and subsequent isomerizations are not infrequently observed.…”
Section: Experimental Methodsmentioning
confidence: 99%